Shaping Education and 21st Century Skills with Futures Literacy: The Futures of Teacher Education in Kenya 2050 - Karjalainen, Joni; Miettinen, Sari; Haapasaari, Osku; Kaskinen, Juha (Finland, 2026)
Finland Futures Research Centre (FFRC) of the University of Turku collaborates with the University of Helsinki, University of Nairobi, and Strathmore University in the Research-based and Future-oriented Curriculum Review and Development for Teacher Education (REFORD) project (2022–2024). The project is co-funded by the Global Innovation Network for Teaching and Learning (GINTL).
The project aims to support Kenyan students to acquire skills needed in 21st century life and the labour market. In Kenya, the Competency Based Curriculum (CBC) was launched for basic education in 2017. The current focus is on rolling out CBC in higher education institutions (HEIs) and teacher education. In addition, the research conducted under REFORD aims to specifically strengthen the design of curricula, improve the quality of delivery of teacher preparation programmes, and thus, strengthen the preparedness of the higher education institutions to implement the CBC.
In this report, authored by the FFRC, the authors examine data uncovered during the project from the perspective of futures studies. The analysis contributes to debates on the needs of students and teachers, 21st century competences, synergies and interruptions in CBC between educational levels, standard of teacher education and university programmes in relation to futures phenomena. The report highlights ways in which the constantly evolving futures horizon is affecting the landscape of Kenyan educational policy and provides information on how education in the Global South can meet aspirations of sustainability.
The outputs of the report support the achievement of Sustainable Development Goal (SDG) 4 to ensure inclusive and equitable quality education and promote lifelong learning opportunities for all. To sustain our 21st century lives, educational structures need to provide learners with relevant competences, models, and a mindset that recognizes the various future opportunities and challenges we are facing.